Complete mitochondrial genome of the gate-keeper ant Colobopsis nipponica (Wheeler, W.M., 1928) (Formicidae: Hymenoptera) - Jonghyun Park; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2021)
Colobopsis ants are unique ants known for their phragmotic behavior. We have completed the mitochondrial genome of Colobopsis nipponica (Wheeler, W.M., 1928) as the first mitochondrial genome of the genus. The mitogenome is 17,431 bp long and 19.4% in GC ratio, which is the third longest mitochondrial genome in subfamily Formicinae. It contains 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a large 1534 bp long control region. Both gene order and phylogenetic analysis agree with the recent elevation of Colobopsis from subgenus to genus.